2021
DOI: 10.1136/bmjnph-2020-000225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraprocessed food intake on cardiometabolic risk is mediated by diet quality: a cross-sectional study

Abstract: ObjectiveTo examine the effect of the consumption of ultraprocessed food on diet quality, and cardiometabolic risk (CMR) in an occupational cohort.DesignCross-sectional.SettingOccupational cohort.Participants53 163 British police force employees enrolled (2004–2012) into the Airwave Health Monitoring Study. A total of 28 forces across the UK agreed to participate. 9009 participants with available 7-day diet record data and complete co-variate data are reported in this study.Main outcome measuresA CMR and Dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
1
17
2
Order By: Relevance
“…Since Monteiro et al proposed the NOVA classification to categorize foods based on the degree of processing [4], several studies have been conducted to estimate the level of consumption of UPF and its association with several health markers [24,35,52,67,120] as well as with disease risk and mortality [55,59,87,121,122], adjusting the models for energy intake and other potential confounding factors. It was hypothesized that a high level of UPF consumption may represent a health issue, being associated with weight gain and worsening of cardiovascular risk factors such as high waist circumference and low HDL cholesterol [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since Monteiro et al proposed the NOVA classification to categorize foods based on the degree of processing [4], several studies have been conducted to estimate the level of consumption of UPF and its association with several health markers [24,35,52,67,120] as well as with disease risk and mortality [55,59,87,121,122], adjusting the models for energy intake and other potential confounding factors. It was hypothesized that a high level of UPF consumption may represent a health issue, being associated with weight gain and worsening of cardiovascular risk factors such as high waist circumference and low HDL cholesterol [11].…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-processed foods, that is, food products that are created from substances extracted from foods or derived from food constituents [ 14 ], contribute on average greater than half of energy intake in the general U.S. population [ 15 ]. Consistent evidence across countries indicates that ultra-processed food intake is associated with select nutrients, including lower intake of fiber [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]; higher total and saturated fat [ 16 , 17 , 18 , 19 , 20 , 23 ]; and higher free, added, or total sugar [ 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 ] in general population samples. Additionally, four studies have demonstrated an inverse relation of ultra-processed foods with overall diet quality [ 18 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent evidence across countries indicates that ultra-processed food intake is associated with select nutrients, including lower intake of fiber [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]; higher total and saturated fat [ 16 , 17 , 18 , 19 , 20 , 23 ]; and higher free, added, or total sugar [ 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 ] in general population samples. Additionally, four studies have demonstrated an inverse relation of ultra-processed foods with overall diet quality [ 18 , 26 , 27 , 28 ]. Consumption of ultra-processed foods may adversely affect overall diet quality via excess intake of highly processed discretionary foods and also by displacing intake of unprocessed, whole plant foods; one study found that greater consumption of ultra-processed food was related to greater intake of sugar-sweetened beverages and processed meat, as well as lower intake of fruits/vegetables, nuts/seeds/legumes, and fish in a general population sample [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intake of ultra-processed foods has been widely linked to a greater cardiometabolic risk and mortality [ 77 , 78 , 79 , 80 ] and should thus not only be avoided among the general population but also among people with CD [ 81 , 82 ]. Therefore, the reduction of these kind of foods should also be another goal of all nutritional interventions performed in the celiac people.…”
Section: Discussionmentioning
confidence: 99%